Building Competitive Advantage: Copra Marketing Strategy with SWOT Analysis Approach - Halek Mu'min; Eliagus Telaumbanua; Ridwan Sya’rani; Badirun Basir; Ilma Wulansari Hasdiansa (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
The research aims to find out how the Business Marketing Strategy uses SWOT analysis. The research method used in this research is qualitative research with a descriptive approach. The data used are primary data and secondary data. Primary data is obtained from direct observation and from farmers providing information. Researchers collected information directly by conducting interviews. Secondary data was obtained from the community of Tugondeng Village, Herlang Subdistrict, Bulukumba Regency. Based on the results of research analysis using SWOT matrix that combines strengths, weaknesses, opportunities and threats, the matrix can produce four sets of possible alternative strategies. By using SWOT analysis, it can be obtained that copra farmers can take alternative strategies ST, WT, SO and WO. In describing the research results, the SWOT matrix is used by analyzing the internal and external factors carried out by providing an overview of the strengths, weaknesses, opportunities and threats possessed by copra farmers.